Urinary Angiotensinogen as a Novel Early Biomarker of Intrarenal Renin–Angiotensin System Activation in Experimental Type 1 Diabetes - Masumi Kamiyama (Journal of Pharmacological Sciences, 2012)
Urinary excretion of albumin (UAlb) is used clinically as a marker of diabetic nephropathy (DN). Although DN was thought to be a unidirectional process, recent studies demonstrated that a large proportion of patients diagnosed with DN reverted to normoalbuminuria. Moreover, despite the normoalbuminuria, one-third of them exhibited reduced renal function even during the microalbuminuric stage. This study was performed to investigate whether urinary angiotensinogen (UAGT) level may serve as a useful marker of the early stage of experimental type 1 diabetes (T1DM). T1DM was induced by a single intraperitoneal injection of streptozotocin. Control mice were injected with citrate buffer. Two days after streptozotocin injection, half of the mice received continuous insulin treatment. Our data showed that UAlb excretion was increased 6 days after streptozotocin injection compared to controls, whereas UAGT excretion was increased at an earlier time point. These increases were reversed by insulin treatment. The UAGT to UAlb ratio was increased in diabetic mice compared to control mice. Furthermore, the increased AGT expression in the kidneys was observed in diabetic mice. These data suggest that UAGT might be useful as a novel early biomarker of activation of the renin–angiotensin system in experimental type 1 diabetes. Keywords:: streptozotocin-induced type 1 diabetic mice, angiotensinogen, biomarker, renin–angiotensin system, diabetic nephropathy